Identifying clinical correlates for suicide among epilepsy patients in South Korea: A case–control study. (4th November 2015) - Park, Sung‐Jin; Lee, Hochang Benjamin; Ahn, Myung Hee; Park, Subin; Choi, Eun Ju; Lee, Hoon‐Jin; Ryu, Han Uk; Kang, Joong‐Koo; Hong, Jin Pyo
Summary: Objective: Suicide is a major cause of premature mortality in patients with epilepsy. We aimed to identify the clinical correlates of suicide in these patients. Methods: We conducted a matched, case–control study based on a clinical case registry of epilepsy patients (n = 35, 638) treated between January 1994 and December 2011 at an academic tertiary medical center in Seoul, Korea. Each epilepsy patient in the suicide group (n = 74) was matched with three epilepsy patients in the nonsuicide group (n = 222) by age, gender, and approximate time at first treatment. The clinical characteristics of the patients in both groups were then compared. Results: In a univariate analysis, seizure frequency during the year before suicide, use of antiepileptic drug polytherapy, lack of aura before seizure, diagnosis of temporal lobe epilepsy, use of levetiracetam, psychiatric comorbidity, and use of antidepressants were all significantly higher in the suicide group than in the nonsuicide group. Multivariate analysis revealed that a high seizure frequency (odds ratio [OR] 3.3, 95% confidence interval [CI] 1.04–10.2), a lack of aura before seizure (OR 4.0, 95% CI 1.7–9.3), temporal lobe epilepsy (OR 3.7, 95% CI 1.6–8.6), and use of levetiracetam (OR 7.6, 95% CI 1.1–53.7) and antidepressants (OR 7.2, 95% CI 1.5–34.1) were all associated with a higher probability of suicide. Significance: Patients with temporal lobe epilepsy who experience seizures weekly or more frequently, experience a lack of aura, use levetiracetam, or take antidepressants are all at a higher risk of suicide and should be monitored closely.